Improving Creative Thinking Skills by Using the Reciprocal Teaching Model Assisted by the Geogebra Application of Class XI Mas Al Washliyah 12 Perbaungan Students - Rahmadani, Suci; Saragih, Risna Mira Bella; Matondang, Khoiruddin (Universitas Negeri Medan, 2024)
The ability to think creatively is the ability to generate new ideas or ideas in producing ways of solving problems, even producing new ways as alternative solutions. Creative thinking is very important in learning mathematics. The results of the study in the control class, namely classes using conventional learning models obtained pretest data with an average of (36%) and posttest data of (52%). While the experimental class is a class that uses creative thinking skills with a reciprocal teaching learning model assisted by the Geogebra application. Pretest data obtained an average score (18%) and posttest data obtained an average score (70%). The results of the study (1) rcalculate = 0.000 and rtabel value = 0.355 can be seen that the value of rcalculate â‰¤ rtabe so that it can be concluded that in this study there was an increase in creative thinking skills using a reciprocal teaching model assisted by Geogebra application to the linear inequality material of two variables in students using conventional model